Analisis Kemampuan Guru Kejuruan SMK Sarolangun dalam Mengintegrasikan Keterampilan Abad 21 Melalui Persepsi Pimpinan Sekolah - Dessy Marlyna; Jonni Mardizal; M. Giatman; Waskito (Postgraduate, University of Mataram, 2025)
This study aims to analyze the ability of vocational teachers in Sarolangun to integrate 21st century skills based on school leaders’ perceptions. A descriptive quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM) was employed, involving 110 respondents from 24 vocational high schools in Sarolangun Regency. Results revealed that teachers demonstrated high proficiency in critical thinking and innovation (82.64), information literacy (82.64), and communication and collaboration skills (79.85). Structural analysis identified significant relationships between skill aspects, with information literacy exerting the strongest influence on critical thinking and problem solving (path coefficient 0.788). The research model explained 67.2% of the variation in teachers’ technological literacy skills. The findings conclude that developing 21st century skills among vocational teachers requires a holistic and comprehensive approach to teacher training and professional development, as these skills are highly interrelated.